(untitled) (Simbiótica. Revista Eletrônica, 2026)
The deficit of sanitation and its impact on health is a reality of a significant part of the Brazilian population. However, this inequality is not equitably distributed in society, as there is a racial profile of those most vulnerable and victimized by unsanitary environmental conditions. Although it is a social issue, this subject has still been neglected as a sociological problem. Thus, based on exploratory-level bibliographic research and the analysis of current data on access to sanitation and morbidity/mortality from diseases related to inadequate environmental sanitation according to color/race, this paper includes the factor of race on sanitation and (environmental) health discussion from a political-historical perspective. The results show that since Colonial Brazil there is a continuum of sanitary experiences of the Black population marked by the lack of access to sanitation services and their impact on the environmental health of this population. As a result, every hour and a half, a Black person dies for not having adequate sanitation in Brazil, a reality that results from the relationship between State, institutional racism and environmental racism, contributing to the genocide of the Brazilian Black population. As such, perspectives and measures that place this topic in the political and research agendas are urgent.